Anti-Inflammatory and Antiosteoclastogenic Activities of Parthenolide on Human Periodontal Ligament Cells In Vitro. (24th December 2014) - Zhang, Xufang; Fan, Chen; Xiao, Yin; Mao, Xueli
Abstract : Periodontitis is an inflammatory disease that causes osteolysis and tooth loss. It is known that the nuclear factor kappa B (NF- κ B) signalling pathway plays a key role in the progression of inflammation and osteoclastogenesis in periodontitis. Parthenolide (PTL), a sesquiterpene lactone extracted from the shoots of Tanacetum parthenium, has been shown to possess anti-inflammatory properties in various diseases. In the study reported herein, we investigated the effects of PTL on the inflammatory and osteoclastogenic response of human periodontal ligament-derived cells (hPDLCs) and revealed the signalling pathways in this process. Our results showed that PTL decreased NF- κ B activation, I- κ B degradation, and ERK activation in hPDLCs. PTL significantly reduced the expression of inflammatory (IL-1 β, IL-6, and TNF- α ) and osteoclastogenic (RANKL, OPG, and M-CSF) genes in LPS-stimulated hPDLCs. In addition, PTL attenuated hPDLC-induced osteoclastogenic differentiation of macrophages (RAW264.7 cells), as well as reducing gene expression of osteoclast-related markers in RAW264.7 cells in an hPDLC-macrophage coculture model. Taken together, these results demonstrate the anti-inflammatory and antiosteoclastogenic activities of PTL in hPDLCs in vitro . These data offer fundamental evidence supporting the potential use of PTL in periodontitis treatment.